2013
DOI: 10.1093/jxb/ert223
|View full text |Cite
|
Sign up to set email alerts
|

A novel Arabidopsis MYB-like transcription factor, MYBH, regulates hypocotyl elongation by enhancing auxin accumulation

Abstract: Critical responses to developmental or environmental stimuli are mediated by different transcription factors, including members of the ERF, bZIP, MYB, MYC, and WRKY families. Of these, MYB genes play roles in many developmental processes. The overexpression of one MYB gene, MYBH, significantly increased hypocotyl elongation in Arabidopsis thaliana plants grown in the light, and the expression of this gene increased markedly in the dark. The MYBH protein contains a conserved motif, R/KLFGV, which was implicated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
40
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 51 publications
(42 citation statements)
references
References 45 publications
2
40
0
Order By: Relevance
“…According to the report of Collett, Harberd, and Leyser (), the auxin levels in wild‐type Arabidopsis were optimal for hypocotyl extension, whereas the extension was suppressed after spraying exogenous auxin. A novel Arabidopsis MYB‐like transcription factor, MYBH, regulated hypocotyl elongation by enhancing auxin accumulation (Kwon et al., ). In our results, IAA soaking significantly promoted ZmMYB59 expression in mesocotyls while reduced its expression in roots.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to the report of Collett, Harberd, and Leyser (), the auxin levels in wild‐type Arabidopsis were optimal for hypocotyl extension, whereas the extension was suppressed after spraying exogenous auxin. A novel Arabidopsis MYB‐like transcription factor, MYBH, regulated hypocotyl elongation by enhancing auxin accumulation (Kwon et al., ). In our results, IAA soaking significantly promoted ZmMYB59 expression in mesocotyls while reduced its expression in roots.…”
Section: Discussionmentioning
confidence: 99%
“…GA 3 significantly enhanced the elongation of the first internode in Hong Mang Mai, a wheat variety tolerant to deep-seeding conditions (Chen et al, 2001(Chen et al, , 2003 (2000), the auxin levels in wild-type Arabidopsis were optimal for hypocotyl extension, whereas the extension was suppressed after spraying exogenous auxin. A novel Arabidopsis MYB-like transcription factor, MYBH, regulated hypocotyl elongation by enhancing auxin accumulation (Kwon et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…In both cases, loss of the transcriptional regulators results in increased H 2 O 2 levels and decreased cell size, indicating that the biochemical action of H 2 O 2 in roots and leaves on cell enlargement is conserved. Notably, UPB1 was shown to act independently from plant hormones, while overexpression of KUA1 is accompanied by an increase in auxin (Kwon et al, 2013). As KUA1 and UPB1 show no homology, it indicates that plants evolved diverse transcriptional regulators to control POXs.…”
Section: Transcriptional Regulation Of Ros Homeostasis During Leaf Exmentioning
confidence: 99%
“…9 Additionally, MYBH/KUA1 expression is regulated by the circadian clock and this MYBH/ KUA1 transcription factor regulates cell expansion, hypocotyl elongation, and leaf senescence in the plant. [14][15][16] Currently, we have found that AtMYBD expression is also controlled by diurnal regulation, see ref. 17 , and this implies that the AtMYBD transcription factor may function to control downstream processes in a circadian clock-dependent manner.…”
mentioning
confidence: 99%